Analysis of Ground Fault Relay Settings on 150 kV Short-Circuit Faults at the Paya Pasir Substation - B. Siahaan, Alfi Santun; Dino Erivianto; Parlin Siagian (Bahasa Indonesia, 2026)
Single line-to-ground faults are among the most frequently occurring disturbances in high-voltage transmission systems and are strongly influenced by the sensitivity settings of the Ground Fault Relay (GFR). This study aims to analyze the suitability of ground fault relay settings in response to short-circuit faults in the 150 kV transmission system at Paya Pasir Substation. The research method involves evaluating existing relay settings on feeder bays, bus couplers, and power transformers, then comparing them with calculation standards based on 7% of the smallest short-circuit capacity (CCC). To obtain optimal relay settings, power system simulations were conducted using ETAP version 19.0.1 by modeling the network in a single-line diagram and analyzing single line-to-ground faults. The results show that most existing GFR settings do not meet protection sensitivity standards, with 60% of feeder bay settings classified as unsuitable. After ETAP simulation and protection parameter adjustments, improved relay sensitivity and selectivity were achieved, ensuring proper protection coordination among feeders, busbars, and power transformers. Therefore, ETAP simulation is proven to be an effective tool for evaluating and optimizing ground fault relay settings in a 150 kV transmission system.